Extra iron for baby pigs - Koch, B.A.; Allee, G.L.; Schoneweis, D.A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Ten mg. of iron per day fed orally 24 days in addition to 150 mg. injected when pigs were 3 days old did not significantly increase Hb of baby pigs. Neither did it increase average daily gain or weight-per-day-of-age at 32 days. We saw no symptoms of iron toxicity in treated pigs.
Swine Industry Day 1975 is known as Swine Day, 1975
Keywords: Swine; Iron; Hemoglobin; Toxicity